Multimedia for Cultural Heritage First International Workshop, MM4CH 2011, Modena, Italy, May 3, 2011, Revised Selected Papers - Grana, Costantino; Cucchiara, Rita (Communications in Computer and Information Science,, 2012)
This book constitutes the revised selected papers from the First International Workshop on Multimedia for Cultural Heritage, MM4CH 2011, held in Modena, Italy, on May 3, 2011. The 8 full papers and 9 poster papers included in this volume were carefully reviewed and selected from 25 submissions. In addition, the book contains a paper resuming the outcome of the discussion session. The workshop aimed on creating a profitable informal working day to discuss hot topics in multimedia, with special application to cultural heritage. The papers of the oral session are divided in topical sections named interaction and analysis and management.